Pengaruh Citra Merek, Kualitas Produk, Harga, dan Promosi Terhadap Keputusan Pembelian Indomie Pada Konsumen Maximart Thamrin Plaza Medan - Chrisjunian Chrisjunian; Robinhot Gultom; Tya Wildana Hapsari Lubis (Jurnal Wira Ekonomi Mikroskil, 2023)
This study aims to determine and analyze the effect of Brand Image, Product Quality, Price, and Promotion on Purchase Decisions for Indomie brand instant noodle products to the consumers of  hypermarket Maximart Thamrin Plaza Medan. This study used a purposive sampling technique carried out by distributing questionnaires online using a Google form to 100 samples, namely consumers of the Maximart Thamrin Plaza Medan hypermarket who had purchased Indomie instant noodle products. The data analysis method used in this study is multiple linear regression. Partial testing (t test) show that the variables Brand Image and Price have effects on purchasing decisions, while Product Quality and Promotion do not affect purchasing decisions for Indomie brand instant noodle products at the Maximart Thamrin Plaza Medan hypermarket. Furthermore, the simultaneous results (F test) shows that the four independent variables (Brand Image, Product Quality, Price, and Promotion) influence the dependent variable (Purchasing Decision). Adjusted R2 shows that the variables Brand Image, Product Quality, Price, and Promotion can explain variations in the Purchase Decision variable by 61% and the remaining 39% is explained by other variables that are not examined in this study.